Determinants of dental caries in children in the Middle East and North Africa region: a systematic review based on literature published from 2000 to 2019 - Amal Elamin; Malin Garemo; Anzelle Mulder (BMC, 2021)
Abstract Background Dental caries risk factors have been expanded to not only emphasize biology, dietary and oral habits but also broader social determinants such as socioeconomic factors and the utilization of health services. The aim was to review sociobehavioural/cultural and socioeconomic determinants of dental caries in children residing in the Middle East and North Africa (MENA) region. Methods A search was conducted in the PubMed/Medline database and Google Scholar to identify studies published from 2000 to 2019 covering children using key search terms. In the initial stages, titles, abstracts and, if needed, full articles were screened for eligibility. In the final stage, all included articles were reassessed and read, and relevant data were extracted. Results Out of 600 initial articles, a total of 77 were included in this review, of which 74 were cross-sectional, 2 were longitudinal and one was a case-control study. The studies included a total of 94,491 participants in 14 countries across the MENA region. A majority used the World Health Organization scoring system to assess dental caries. The caries prevalence ranged between 17.2% and 88.8%, early childhood caries between 3% and 57% and decayed missing filled teeth (dmft) varied between 0.6 and 8.5 across the various age groups. Increased age, low maternal education, low overall socioeconomic status, decreased frequency of tooth brushing, low parental involvement, poor oral habits, infant feeding practices and sugar consumption were among the most prevalent determinants for increased risk of caries in the reviewed studies. Conclusions Dental caries was found to be high among children in many of the studies published from MENA. The key determinants of dental caries were found to include factors related to child characteristics, family background, oral hygiene and infant feeding and eating habits. The high dental caries prevalence emphasises the need to address the prevailing modifiable sociobehavioural and socioeconomic determinants by translating them into effective oral health prevention policies and programmes.